Oral health-related quality of life of children with oral clefts and their families - Gabriela Mendonça Rando; Paula Karine Jorge; Luciana Lourenço Ribeiro Vitor; Cleide Felício Carvalho Carrara; Simone Soares; Thiago Cruvinel Silva; Daniela Rios; Maria Aparecida Andrade Moreira Machado; Maria Beatriz Gavião; Thais Marchini Oliveira (University of São Paulo, 2018)
Abstract Oral health problems can influence people's Quality of Life (QoL) because of pain, discomfort, limitations, and other esthetics problems, affecting their social life, feeding, daily activities, and the individual's well-being. Objective: To compare oral health-related quality of life (OHRQoL) of children with and without oral clefts and their families. Materials and Methods: 121 children aged from 2 to 6 years, from both sexes, enrolled in the treatment routine of the Pediatric Dentistry Clinics of a Dental School and a Hospital for Cleft Treatment were divided into two groups: Group 1 - children with cleft lip and palate; Group 2 - children without cleft lip and palate. The OHRQoL was assessed using the validated Portuguese version of the Early Childhood Oral Health Impact Scale (B-ECOHIS). The questionnaire was answered individually, only once, at a private place. Mann-Whitney U test was used to verify differences between groups. Spearman's Rho test was used to associate sex and age with quality of life. The level of significance was set at 5% (p<0.05). Results: According to the parents' perception on the OHRQoL of children with and without cleft lip and palate, oral health of children with oral clefts (Group 1) had a statistically significant impact on OHRQoL. The correlation of sex with impact on OHRQoL did not show statistically significant differences. On the other hand, the higher the age the higher the impact on QoL. Conclusions: The group comparison revealed that the cleft lip and palate negatively impacted on OHRQoL of 2 to 6-year-old children and their parents.